AB0506 Enhanced improvement in fatigue from RA treatment with secukinumab: An application of IRT methodology. (23rd January 2014) - Gnanasakthy, A.; Kosinski, M.; Durez, P.; Mallya, U.; Mpofu, S.
Abstract : Background: Fatigue is common in RA and its absence characterizes disease remission 1 . Between 40% and 80% of RA patients visiting specialists clinics with active disease also have clinically relevant fatigue 1-4 . In addition, patients experiencing greater levels of fatigue are markedly more disabled than patients experiencing less fatigue 5 . The recognition of fatigue as an important treatment outcome has prompted EULAR and the ACR expert panels to add fatigue to the core set of recommended endpoints for RA clinical trials 6 . Two instruments that have been used to measure fatigue in RA treatment studies are the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) and the SF-36v2 vitality (VT) scale. Objectives: To determine if a composite fatigue index derived from cross-calibrating the items of the FACIT-F and SF-36v2 VT scales using IRT methods improves the ability to detect treatment effects in RA. Methods: Adult RA patients (n=237) on methotrexate were randomized equally to receive monthly s.c. injections of secukinumab 25mg, 75mg, 150mg, 300mg or placebo. The SF-36v2 and FACIT-F were administered at baseline and weeks 2, 4, 8, 12, and 16. A generalized partial credit interactive response technology (IRT) model was used to cross-calibrate the items of the SF-36 VT and FACIT-F scales and weighted maximum likelihood estimation was used to score a composite PF index. Change scores from baseline to week 16 were calculated for the composite fatigue index and the SF-36 VT and FACIT-F scales. Analysis of variance and effect sizes (mean change score divided by SD) were used to evaluate and compare the sensitivity of each fatigue measure in responding to secukinumab treatment. A ratio of F-statistics was calculated to determine the relative validity (RV) of each fatigue measure in responding to treatment in both a within groups (difference from 0) and between groups (treatment vs placebo) analysis. Results: From within groups analysis the composite fatigue index was found to be the most responsive to secukinumab treatment for all 4 secukinumab dose groups compared to the SF-36 VT and FACIT-F scales. Across secukinumab dose groups the effect size for the composite fatigue index was 11%>93% larger than the effect sizes observed for the SF-36 VT and FACIT-F scales. In addition, the F-statistics testing the difference in change score from 0 within each of the secukinumab dose groups was largest for the composite fatigue index, indicating a greater response to treatment. In the between groups analyses, both the 75mg (mean difference of 3.3 points, F=3.9, p<0.05) and 150mg (mean difference of 3.5 points, F=5.1, p<0.05) secukinumab groups showed significantly greater improvement in fatigue scores on the composite index compared to placebo. No significant differences in change scores between the 75mg and 150mg dose groups and placebo was observed with either the SF-36 VT or FACIT-F scales alone. Conclusions: IRT methods offer a promising approach to improving the measurement of fatigue in treatment studies of RA. References: Pinals RS et al. Arthritis Rheum 1981;24:1308-15. Belza BL. J Rheumatol 1995;22:639-43. Belza BL et al. Nurs Res 1993;42:93-9. Wolfe F et al. J Rheumatol 1996;23:1407-17. Rupp I et al. Arthritis Rheum 2004;51:578-85. Aletaha D et al. Ann Rheum Dis 2008;67:1360-4. Disclosure of Interest: A. Gnanasakthy Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation, M. Kosinski Consultant for: Novartis Pharmaceuticals Corporation, P. Durez: None Declared, U. Mallya Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation, S. Mpofu Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG